Ω-Hydroxylation of α-tocopheryl quinone reveals a dual function for cytochrome P450-4F2 in vitamin E metabolism. Issue 20 (1st November 2018) - Taylor, Luke; Krueger, Nick; Malysheva, Olga; Atkinson, Jeffrey; Parker, Robert S.
Graphical abstract: Abstract: α-Tocopherol (α-TOH) is the primary lipophilic radical trapping antioxidant in human tissues. Oxidative catabolism of α-tocopherol (αTOH) is initiated by ω-hydroxylation of the terminal carbon (C-13) of the isoprenoid sidechain followed by oxidative transformations that sequentially truncate the chain to yield the 2, 5, 7, 8-tetramethyl(3′carboxyethyl)-6-hydroxychroman (α-CEHC). After conjugation to glucuronic acid, 3′-carboxyethyl-6-hydroxychroman glucuronide is excreted in urine. We report here that the same enzyme that accomplishes this task, the cytochrome P450 monooxygenase CYP-4F2, can also ω-hydroxylate the terminal carbon of α-tocopheryl quinone. A standard sample of ω-OH-α-tocopheryl quinone (ω-OH-α-TQ) was synthesized as a mixture of stereoisomers by allylic oxidation of α-tocotrienol using SeO2 followed by double-bond reduction and oxidation to the quinone. After incubating human liver microsomes or insect cell microsomes expressing only recombinant human CYP-4F2, cytochrome b5, and NADPH P450 reductase with d 6 -α-tocopheryl quinone ( d 6 -αTQ), we showed that the ω-hydroxylated (13-OH) d6 -α-TQ was produced. We further identified the production of the terminal carboxylic acid d 6 -13-COOH-αTQ. The ramifications of this discovery to the understanding of tocopherol utilization and metabolism, including the quantitative importance of the αTQ-ω-hydroxylase pathway in humans, are discussed.